Pengaruh Pemberian Boiled Egg terhadap Peningkatan Kadar Hemoglobin Remaja Putri Anemia di SMP Baiturrahman Kota - jafna saniadji; Iriyanti Harun; Galuh Chandra Irawan (Jurnal Ilmiah Gizi dan Kesehatan (JIGK), 2026)
Anemia in adolescent girls often occurs due to low intake of iron, vitamins, and protein, which can reduce academic performance and quality of life. Boiled eggs are an easily accessible and affordable source of iron and animal protein. This study aims to determine the effect of boiled egg consumption on hemoglobin (Hb) levels in anemic adolescent girls at SMP Plus Baiturrahman in Bandung City. The study design used a quasi-experimental two-group pretest-posttest approach with 50 female students, divided into an intervention group and a control group. The intervention group received one boiled egg daily for 14 days. The results showed that the Hb levels in the intervention group increased from 9.372 g/dL to 10.096 g/dL, while the control group decreased from 13.756 g/dL to 13.668 g/dL. The Wilcoxon test indicated a significant effect in the intervention group (p = 0.000), and the Mann-Whitney test showed a significant difference between groups (p = 0.000). Boiled eggs are effective as a simple strategy for preventing anemia in schools.